2015
DOI: 10.1109/twc.2015.2457900
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Eigenmode Transmission for the MU-MIMO Downlink in Rician Fading

Abstract: Abstract-In this paper, we study the achievable ergodic sum-rate of multiuser multiple-input multiple-output downlink systems in Rician fading channels. We first derive a lower bound on the average signal-to-leakage-and-noise ratio by using the Mullen's inequality, and then use it to analyze the effect of channel mean information on the achievable ergodic sum-rate. A novel statistical-eigenmode space-division multiple-access (SE-SDMA) downlink transmission scheme is then proposed. For this scheme, we derive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…Assume that each user is equipped with a single antenna element [3]. Additionally, the number of the BS antenna elements is assumed to be larger than that of users ( ≥ ); and the power is equally allocated among all users [11,12].…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Assume that each user is equipped with a single antenna element [3]. Additionally, the number of the BS antenna elements is assumed to be larger than that of users ( ≥ ); and the power is equally allocated among all users [11,12].…”
Section: System Modelmentioning
confidence: 99%
“…It was found that when the users are homogeneously distributed and the number of antenna elements is large enough ( → ∞), the SLNR is asymptotically equal to SINR. In [11], an efficient statistical Eigen-mode space division multiple access (SE-SDMA) scheme for downlink ergodic sum-rate analysis based on SLNR was proposed. To maximise the approximate ergodic sum-rate capacity, authors in [12] designed an optimal beamforming vector for each user based on a three-dimensional beamforming algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above superiorities over OFDM, OQAM/FBMC is being considered as a promising technique for cognitive radio [8], professional mobile radio (PMR) evolution [9], and 5G cellular networks [10], [11]. As another promising technique in future communication systems, multiple-input multipleoutput (MIMO) is able to increase the system throughput and the link reliability [12], [13]. Therefore, it is believed that the successful combination of MIMO and OQAM/FBMC is important and is envisioned to achieve higher spectral efficiency [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its extremely short wavelengths, mmWaves are unable to propagate over large distances, and are primarily envisaged to operate in small-cellular scenarios, where there is a considerably higher probability of a terminal experiencing LoS propagation. To this end, several investigations have examined the performance of massive MIMO with Ricean fading [10][11][12][13], including studies which consider variability in the Ricean K-factors across multiple terminals [9,14].…”
Section: Introductionmentioning
confidence: 99%